Use of bacteriophages as an alternative in the control of bacterial infections (Research, Society and Development, 2022)
WHO predicts that, by 2050, infections caused by resistant bacteria will cause about 10 million deaths annually. Considered a public health crisis neglected worldwide, bacterial resistance (AMR) has been aggravated by the indiscriminate use of antimicrobials, which can be transmitted from one organism to another, favoring the emergence of pan-resistant bacteria. From this scenario, it is necessary to search for alternative treatment methodologies, such as phage therapy, which is based on the use of the natural replication mechanism of bacteriophages to cause bacterial cell lysis, which can be an excellent option for the treatment and control of infections caused by resistant bacteria. Therefore, this work aimed to highlight the potential of phage therapy in the fight against such infections, where this technique has shown positive and hopeful results in the fight against infections in several sites and by different routes of administration, even allowing the treatment of infections caused by biofilm-producing bacteria. It is, therefore, an extremely advantageous technique, using extremely specific viruses regarding the target microorganism, which ends up reducing the risks of toxicity, allergic reactions and dysbiosis. In addition, the combined use of bacteriophages and antibiotics presents synergistic results that allow the reduction of the antimicrobial loading dose and a greater effectiveness in the treatment. However, as phage therapy still does not have specific protocols for its use, further studies related to its implementation are needed, so that it is possible to enjoy this alternative treatment more in the future.